A CONSTITUIÇÃO DOS SISTEMAS DE ENSINO NO ESTADO DE MATO GROSSO DO SUL: AUTONOMIA E DESCENTRALIZAÇÃO - ANDRÉA BRAGA SODRÉ ROCHA (2023)
This research is part of the line of research “History, Politics, Education”, of the Graduate Program in the Federal University of Mato Grosso do Sul (PPGEdu/FAED/UFMS), has as its object the analysis of the regulations of the municipalities that opted for the creation of its municipal education systems. The general objective is to analyze, through legislation and documents, the option of the municipalities of Mato Grosso do Sul for the creation of their municipal education systems, in the period from 1997 to 2019. The specific objectives proposed were: 1 – To analyze the processes of decentralization and autonomy present in Brazilian federalism and its implications for the creation of education systems; 2 - Examine the guidelines established for the institution and implementation of the education systems in the state of Mato Grosso do Sul; and, 3 - Survey the number of municipalities in Mato Grosso do Sul that instituted their education systems and the regulations given in relation to the principle of democratic management. The research was based on a bibliographic review, highlighting the productions on the political processes that made it possible for municipalities to choose to create their respective education systems. And for the documentary analysis, documents from the State Council of Education of Mato Grosso do Sul, the Organic Laws of the Municipalities, Ordinances, Resolutions, Municipal Decrees, Municipal Education Plans (2015-2025), regulations of the respective education systems and others were used. documents that are necessary. After the collection, the systematization of these documents was carried out, through which it was concluded that the Federative Constituition of Brazil of 1988, by including the municipality as a federative entity, provided it with relative autonomy, since it participates on unequal terms with the states and the Union, but with the same degree of responsibilities In this scenario, of the 79 municipalities in the state of Mato Grosso do Sul 39 of them chose to create their own education systems. The research verified that all the municipalities that created their own municipal education systems have municipal education councils and their respective municipal education plans.